The Concept of Matchmaking Through Online Matchmaking Bureaus in the Modern Era. Study of Sociological Analysis and Darurah Rules - Mohammad Afandy; Fatmawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research aims to explain the phenomenon of the practice of finding a life partner through the use of online matchmaking sites if analyzed by applying the rules of darurah. In reviewing the discussion, the author used a qualitative approach and purposive sampling technique as an effort to extract data. The research results show that the preference for online matchmaking agencies can be said to be a complementary tool in finding a life partner, meaning that under any circumstances the majority of looking for a partner prefers to look for themselves without using an online matchmaking agency, so this online matchmaking agency is not used as the main tool in finding a life partner. , but rather as a complementary tool to open the gate to a more serious level.